2012
DOI: 10.1186/1471-2431-12-5
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate as a predictor of metabolic dysfunctions in obese children and adolescents

Abstract: BackgroundRecent studies have identified that a higher resting heart rate (RHR) is associated with elevated blood pressure, independent of body fatness, age and ethnicity. However, it is still unclear whether RHR can also be applied as a screening for other risk factors, such as hyperglycemia and dyslipidemia. Thus, the purpose of the presented study was to analyze the association between RHR, lipid profile and fasting glucose in obese children and adolescents.MethodsThe sample was composed of 180 obese childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 35 publications
3
32
0
2
Order By: Relevance
“…Previous results from American and Israeli Industries Study supported our findings [17][19]. In addition, similar relationships were also observed between resting pulse rate and lipid metabolic dysfunctions by Freitas and his colleagues [20], but the correlation was weaker than results from their study (TC: r  = 0.189, TG: r  = 0.215, HDL-C: r  = 0.035, and LDL-C: r  = 0.118). Alternatively, univariate regression analyses showed that resting pulse rate was positively associated with risk of lipid metabolic dysfunctions through dose-response effect ( P for trend <0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Previous results from American and Israeli Industries Study supported our findings [17][19]. In addition, similar relationships were also observed between resting pulse rate and lipid metabolic dysfunctions by Freitas and his colleagues [20], but the correlation was weaker than results from their study (TC: r  = 0.189, TG: r  = 0.215, HDL-C: r  = 0.035, and LDL-C: r  = 0.118). Alternatively, univariate regression analyses showed that resting pulse rate was positively associated with risk of lipid metabolic dysfunctions through dose-response effect ( P for trend <0.05).…”
Section: Discussionsupporting
confidence: 90%
“…This is in contrast to stronger evidence in adults for RHR to be a marker of long term disease. It has been suggested that elevated RHR may be a potential measure to screen children with dyslipidaemia who are at risk of future development of atherosclerosis 22. Further study of the potential role of RHR in predicting disease seems warranted, given that it is a simple measurement to undertake and has associations with cardiometabolic risk factors such as elevated BP, physical inactivity, dyslipidaemia and possibly central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [12,17,18,22,28] have analyzed the association between cardiovascular risk factors and elevated RHR in adolescents, but several aspects remain less clear. For example, previous studies rarely considered the role of clustering of cardiovascular risk factors and its relationship with RHR in children and adolescents.…”
Section: Introductionmentioning
confidence: 98%
“…RHR is emerging as an easily measurable clinical parameter that is a predictive marker of cardiovascular disease (CVD) and mortality [19][20][21]42]. Elevated RHR is associated with higher levels of blood pressure, abdominal obesity, triglycerides, and glucose in children and adolescents [12,17,18,22,28], indicating its potential as a screening tool of cardiovascular risk in children.…”
Section: Introductionmentioning
confidence: 99%